The case of the initial letter : Charles Dickens and the politics of the dual alphabet - Edwards, Gavin; Smith, Andrew; Barton, Anna (Manchester : Manchester University Press, 2020)
The book analyses attempts by Dickens and other nineteenth-century writers to challenge established ways of using the distinction between upper and lower case letters, in the interests of a wider radicalism. It discusses Dickens's satire - on 'Shares' in Our Mutual Friend, on Paul Dombey's position as the 'Son' of Dombey and Son - alongside the proto-modernist typography of suffragist poet Augusta Webster and the work of Marx's translators transforming German conventions of capitalisation into English under the influence of Dickens and Carlyle. Placing these innovations within the history of the dual alphabet from its invention by Carolingian scribes to its rejection by modernist poets and the Bauhaus printers, the book tracks the dual alphabet through Dickens's manuscripts, corrected proofs, and the 'prompt copies' for his public Readings, highlighting distinct ways in which writing, printing and speech produce meaning.
1 Introduction: The case of the initial letter2 Typographic leveling in an age of revolution3 The Land of Liberty4 Dombey -- and Son -- and Daughter5 People, things, and abstractions6 Print capitalism7 Freedom, Equality, Property and Bentham8 Writin'large9 PIP and D O C T O R M A R I G O L D10 Dickens, the suffragists and proto-modernism BibliographyIndex
Description based on CIP data; resource not viewed.
JSTOR
Keywords: Dickens, Charles, -- 1812-1870 -- Criticism and interpretation; Dickens, Charles, -- 1812-1870; English literature -- Political aspects -- Great Britain -- History -- 19th century; Alphabets -- Social aspects -- History -- 19th century; Initials; English literature -- 19th century -- History and criticism; Alphabets (Décoration) -- Aspect social -- Histoire -- 19e siècle.; Littérature anglaise -- 19e siècle -- Histoire et critique; LITERARY COLLECTIONS / English, Irish, Scottish, Welsh; English literature; English literature -- Political aspects; Initials; Great Britain; LITERARY COLLECTIONS / European / English, Irish, Scottish, Welsh; 1800-1899; Criticism, interpretation, etc; History